SURVEY OF THERMAL ENERGY RECOVERY AND REUSE TECHNOLOGIES IN MODERN HVAC SYSTEMS - Yadav, Dr Dinesh (Journal of Global Research in Mathematical Archives(JGRMA), 2026)
HVAC systems have shown that they ought to make use of thermal energy recovery and reuse technology to increase the level of energy efficiency and minimise the impact of buildings on the environment. The systems greatly reduced heating and cooling needs and increased comfort levels in the region by absorbing waste heat from the exhaust air. The heat energy is reclaimed with the assistance of the state-of-the-art equipment, including rotary wheels, fixed plate exchangers, heat pipes and run-around systems, which in conjunction with the constant efficiency of 50-95%, transfer the sensible and latent heat between the airstreams. It also enhances their performance by incorporating IoT-enabled sensing, real-time monitoring, and intelligent control strategies. The ability to continuously control temperature, humidity, and airflow with the assistance of IoT sensors will enable automated ventilation adjustments, maximising performance and minimising energy consumption. Digital Twin technology is an appropriate tool for this model and enables predictive modelling, fault tolerance, and maintenance of the system's optimal behaviour throughout the building's life cycle. All these innovations combined with Building Automation Systems (BAS) and regulatory requirements can steer the HVAC designs to be reliable, comfortable to occupants and ultimately saving energy.